2023
DOI: 10.3390/healthcare11020232
|View full text |Cite
|
Sign up to set email alerts
|

E-Learning Performance Evaluation in Medical Education—A Bibliometric and Visualization Analysis

Abstract: Performance evaluation is one of the most critical components in assuring the comprehensive development of e-learning in medical education (e-LMED). Although several studies evaluate performance in e-LMED, no study presently maps the rising scientific knowledge and evolutionary patterns that establish a solid background to investigate and quantify the efficacy of the evaluation of performance in e-LMED. Therefore, this study aims to quantify scientific productivity, identify the key terms and analyze the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…This provides insights into the specific focus areas and the evolving research landscape in e-learning and medical education, highlighting the growing significance of COVID-19 and its influence on teaching and learning practices in the field. Previous studies also identified a sharp incline in publications in the domain due to the COVID-19 pandemic (Dehnad & Abdekhoda, 2023;Oluwadele et al, 2023;Sweileh, 2021).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This provides insights into the specific focus areas and the evolving research landscape in e-learning and medical education, highlighting the growing significance of COVID-19 and its influence on teaching and learning practices in the field. Previous studies also identified a sharp incline in publications in the domain due to the COVID-19 pandemic (Dehnad & Abdekhoda, 2023;Oluwadele et al, 2023;Sweileh, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…His collaboration with these prolific authors signifies the recognition and respect he has gained among his peers. Previous scholars have identified this collaboration (Oluwadele et al., 2023; Sweileh, 2021) to showcase the interconnectedness of researchers and the collective effort to advance knowledge and practice in e‐learning in medical education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Student achievement in a variety of academic topics is measured by academic performance. Structured assessments, graduation rates, and performance in the classroom are frequently used by educators to gauge student achievement (Oluwadele et al, 2023). E-learning additionally qualifies as the delivery of instructional materials and learning activities using technological tools like computers, cell phones, or mobile systems to enhance both the standard of teaching and the educational process for students (Yang et al, 2023).…”
Section: Theoretical Backgroundmentioning
confidence: 99%